Correction: TiO2/vanadate (Sr10V6O25, Ni3V2O8, Zn2V2O7) heterostructured photocatalysts with enhanced photocatalytic activity for photoreduction of CO2 into CH4. Issue 5 (23rd January 2018) - Yan, Yabin; Yu, Yanlong; Wu, Di; Yang, Yajun; Cao, Yaan
Abstract : Correction for 'TiO2 /vanadate (Sr10 V6 O25, Ni3 V2 O8, Zn2 V2 O7 ) heterostructured photocatalysts with enhanced photocatalytic activity for photoreduction of CO2 into CH4 ′ by Yabin Yan et al., Nanoscale, 2016, 8, 949–958.